Entraves et conséquences de la nationalisation de la main d’œuvre dans le secteur de la pêche artisanale en Mauritanie - Marta Alonso Cabré (L’Année du Maghreb)
In this article based on data collected in the field between June and October 2018, we propose to analyze the social consequences of the prohibition of foreign labor - essentially called «Senegalese» - in the field of artisanal fishing in Mauritanian waters. If it is a question, on the one hand, to show the impact of this decision of the Mauritanian government on the workforce, it is also to give to understand more widely how this political choice leads some Mauritanians to constantly having to prove their identity. Presenting an official identity document is particularly difficult for many, especially those who may be confused with neighboring nationals, but also those whose lives are anchored on the margins of society.